Enhancing Cruise Booking Systems: Integrating Human Expertise with AI through Agile Methods - Jayaram Bhogi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative integration of human expertise with artificial intelligence in cruise booking systems through agile methodologies. The article examines how the synergy between human knowledge and AI capabilities can enhance search optimization in the cruise industry, addressing complex challenges in modern booking platforms. It shows the crucial components of successful human-AI collaboration, including domain expertise, technological integration, and adaptive frameworks. The article presents a comprehensive analysis of implementation strategies, highlighting the importance of well-defined roles, communication protocols, and technical considerations. Through detailed case studies and performance metrics, the article demonstrates the significant improvements achieved in search accuracy, customer satisfaction, and operational efficiency. The findings emphasize the value of agile practices in facilitating continuous system refinement while maintaining the critical balance between automated processes and human oversight. Furthermore, the article explores emerging technologies and future directions in human-AI collaboration, providing insights into the evolving landscape of cruise booking systems and the increasing sophistication of search optimization techniques.